Survivors’ Concerns During the COVID-19 Pandemic: Qualitative Insights From the National Sexual Assault Online Hotline - Elliott, Shannon A. (Journal of interpersonal violence, 2023)
With the onset of the COVID-19 pandemic and the implementation of stay-at-home orders in March 2020, experts warned of the possible threat of increased interpersonal violence among individuals isolated with abusers. Researchers have sought to understand how the pandemic impacted victims primarily through the analysis of administrative data sources, such as hospital and police records. However, the preponderance of this data shows a decrease in formal help-seeking among victims during the pandemic, speaking to an impaired access to services but limiting our understanding of other ways in which the pandemic has affected survivors. To overcome these limitations, we examined data collected about users of the National Sexual Assault Online Hotline (NSAOH). Information was collected through staff based on retrospective recall following one-on-one chat sessions with 470 victims of sexual violence who contacted the NSAOH in the first six months of the pandemic and discussed COVID-19-related concerns. We qualitatively examined open-ended descriptions of COVID-19-related concerns and identified the four most common: (1) mental health concerns, (2) creation or exacerbation of an unsafe living situation, (3) not being able to access services, and (4) not having access to a mandatory reporter or trusted adult. These findings demonstrate the myriad ways in which the pandemic affected the lives of victims of sexual violence and can inform practices for services and practitioners to best meet the needs of survivors moving forward. Specifically, these findings highlight the need for more accessible mental health services and funding for sexual assault service providers, as well as the importance of safety planning, particularly in times of crisis.